Odziedziczona trauma, czyli kobiece doświadczanie pamięci regionalnej na przykładzie Śląska w powieści Ulrike Draesner "Sieben Sprünge vom Rand der Welt" ("Siedem skoków z krańca świata") = An inherited trauma, or the feminine experience of regional memory using the example of Silesia in the novel "Sieben Sprünge vom Rand der Welt" ("Seven jumps from the edge of the world") by Ulrike Draesner - Ratajczak, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper is devoted to the feminine experience of the world and history of the World War II period, with particular emphasis on regional history (Silesia as a palimpsest), as well as the consequences of the war, which turns out to be crucial not only for its direct victims but also for their descendants.
Keywords: II (druga) wojna światowa; II world war; woman; Silesia; borderland; wypędzeni; kobieta; trauma; Śląsk; Kresy